Wybrane aspekty procesów integracji gospodarczej w regionie Azji Południowo-Wschodniej - Kichter-Krysiak, Monika (The Chosen Aspects of Economic Integration Processes in the Region of South-East Asia, 2008)
The article deals with the problem of the chosen aspects of economic integration processes in the region of South-East Asia and includes initial characteristics of this region taking under consideration historic constraints in the region and Asian values, important to understand the processes that take place in the region. The author analyzes, beside generally expressed problem of essence and form of international economic integration, the issue of The Association of South-East Asian Nations (ASEAN) as an attempt to integrate the region . The article shows the origin of ASEAN, its institutional grounds and economic result of integration processes taking place in ASEAN. As a consequence of analysis, the author draws conclusions that despite the potential for development, which comes from the scale of the market, traditional values and the importance of this Association in the international market, the economic development of countries of the region and co-operation in the region is restrained by still low efficiency and slow trade liberalization. What is more, neither the markets of ASEAN member countries nor political situation of some of these countries are fully stable. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 110-124